Pharmacogenetics of VKORC1 in warfarin resistant patients. - Ong, Jacqueline Kai Mei. (2010)
Warfarin is a commonly prescribed anticoagulant that displays wide inter-individual variability in treatment response and dosage. It acts by inhibiting the vitamin K epoxide reductase (VKOR) enzyme in the liver. Genetic variations in vitamin K epoxide reductase complex subunit 1(VKORC1), have been associated with differential dose requirement of warfarin. However, high variability in treatment response is still observed. The hypothesis is that other functional polymorphisms in VKORC1 may influence the enzymatic activity of VKOR, leading to variation in the pharmacodynamics of warfarin. Thus, the aim of this study is to investigate novel polymorphisms in VKORC1 that may influence the activity of VKOR in patients receiving varying warfarin dosages. In this study, the VKORC1 gene was screened for novel polymorphisms in 32 subjects. A total of fifteen mutations were found, of which eight were novel. In particular, 337 G>A, 1849_1850 insertion T and 4851 T>G were found to be present in higher frequencies in the high-dose patients. This exploratory study provides the basis for future studies of the pharmacogenetics of VKORC1 in a larger population.